School support service to a student with intellectual disabilities from a school in the state education network in the municipality of Curuçá-PA (Research, Society and Development, 2022)
The present study aims to analyze the attendance of school support offered to a student with intellectual disabilities from a state public school in Pará, located in the municipality of Curuçá. The theoretical discussion is guided by the Brazilian Constitution of 1988, approaching the historical and political foundations of Special Education and studies on Intellectual Disability, revealing the importance of an inclusive school system that has a sensitive look at the needs of this public in the process. of schooling. Our understanding of the subject is that for an effective implementation of the inclusive education proposal, it is not enough to expand the access of the public to special education in common schools, it is necessary to invest in teacher qualification, in a multidisciplinary team to assist these students, and to review together to the other subjects involved in the school educational process, pedagogical intervention practices in special education. Data collection was carried out based on observations and application of activities developed with the help of adapted pedagogical resources. As results of the analysis, the lack of planning of a teaching work directed to the educational needs of the student, the contributions of the pedagogical resources adapted to reduce the barriers encountered in the student's schooling process and expand her learning capacity, stand out. advances both in the pedagogical and social aspects. Linked to the qualitative approach, the study was carried out through field research of an exploratory nature in a school in the rural area of ​​the state education network, located in Curuçá-PA.